Executive Committee Minutes 2008-02-14 - Academic Senate:::::::::
Presentation for SSU's Production of the Vagina Monologues, Revision to RTP policy, Geography/Global Studies revisions, University 150 (FYE), Ad-Hoc Committee Strategies document